Perceptions of preferred vs. actual constructivist learning environments among secondary students in Selangor - Ibrahim, Hasniza; Kamarulzaman, Wirawani (Asian Scholar Network, 2024)
In the dynamic educational landscape of Malaysia, the transition to constructivist learning environments is a pivotal shift in pedagogical methodologies. This study explores the complexities of constructivist learning environments, particularly in the context of mathematics education among secondary school students in Selangor. The investigation aims to discern differences between students preferred and actual experiences within these innovative educational settings. Specifically, the objectives of the study are 1) to examine the difference between students' perceptions of their preferred and actual constructivist learning environment (CLE), 2) to identify the difference between genders in their perceptions of preferred CLE and 3) to determine the difference between genders in their perceptions of actual CLE. The quantitative analysis of students' perceptions uncovered a significant disparity between their preferred and actual experiences within constructivist learning environments. Despite students' inclination towards such environments, practical implementation fell short of their anticipated standards. Gender differences in students' perceptions were explored, revealing that while there was no significant gender difference in preferred constructivist learning environments, male students perceived a greater frequency of constructivist learning in actual experiences compared to their female counterparts. The identified discrepancies between preferred and actual constructivist learning environments underscore a critical gap in the Malaysian educational landscape. The study advocates for enhanced implementation of constructivist methodologies, aligning with the calls of scholars to bridge observed disparities. The findings contribute valuable insights for policymakers and educators to consider in creating inclusive and effective learning environments. This research serves as a significant contribution to the ongoing discourse on constructivist learning environments in Malaysia, offering guidance for impactful modifications in educational methodologies.